Gender Differences in Outcomes After Primary PCI in Acute Myocardial Infarction - Parvez, Muzdalfa; Khan, Muhammad Idrees; Khan, Naveed Ahmad; Spogmai,; Muhammad , Hafeez; Khattak, Imran Qadar (Indus Journal of Bioscience Research, 2024)
Objective: To investigate gender differences in clinical outcomes after primary percutaneous coronary intervention (PCI) in patients with acute myocardial infarction (AMI), highlighting insights within a Pakistani healthcare context.Methodology: Conducted over ten months at the Hayatabad Medical Complex, Peshawar, this prospective observational study enrolled 300 AMI patients (150 males, 150 females) treated with primary PCI. Key parameters analyzed included AMI type, demographic characteristics, post-procedure complications, and mortality rates. Statistical analysis was conducted using chi-square tests to examine the association between gender and outcome disparities.Results: The findings revealed that men predominantly presented with STEMI, accounting for higher complication rates and adverse outcomes compared to women. Male patients demonstrated a 22% incidence of major adverse cardiac events (MACE), while female patients showed a 14% MACE rate, predominantly among NSTEMI cases. The age distribution for both genders was centered in the 50-70 age range, with no statistically significant association between gender and overall outcomes (p = 0.582). These results align with international trends yet emphasize the need for gender-sensitive approaches in PCI care within Pakistan.Conclusion: The study underscores notable gender disparities in AMI presentation and outcomes following PCI. Men face higher risks, particularly with STEMI, suggesting a critical need for gender-specific protocols in AMI management. These findings support further multi-center research to enhance gender-responsive healthcare strategies in Pakistan.